Highly sulfonated hyper-cross-linked polymers as promising adsorbents for efficient and selective removal of ciprofloxacin from water - Wolska, Joanna; Frankowski, Marcin; Jenczyk, Jacek; Wolski, Lukasz (Elsevier, 2024)
This study aims at the development of novel and highly sulfonated hyper-cross-linked polymers (sHCPs) using facile and one-step synthetic approach, and verification of the potential applicability of the as-synthesized polymers in the adsorptive removal of various antibiotic pollutants under environmentally relevant conditions. The sHCPs synthesized in this work were capable of highly efficient removal of antibiotic pollutants at relatively high (30 mg/L) and low (50 µg/L) initial concentrations, both from a simple as well as complex water matrices. The rate of ciprofloxacin removal and the adsorption capacity observed for the most efficient adsorbent (qe = 757.7 mg/g) were found to be approximately twice higher than that established for other previously reported sulfonated polymers prepared via post-synthetic sulfonation (qe = 476.9 mg/g), and commercial polymer-based adsorbents (e.g. Amberlyst-15, qe = 438.5 mg/g). The highest adsorption capacity was observed at pH close to neutral for polar antibiotic pollutants that contain protonated functional groups and exist in cationic or zwitterion form (e.g. ciprofloxacin and tetracycline). The reported results clearly imply that highly sulfonated hyper-cross-linked polymers are promising candidates for potential practical application for the elimination of organic pollutants from aqueous media, being capable of selective removal of various antibiotics via ionic interaction even in the presence of a great excess of other cations, anions and organic matter naturally existing in environmentally relevant water samples (e.g. river water).
Keywords: porous organic polymers; hyper-cross-linked polymers; sulfonic acid functionalization; antibiotic pollutants; water purification